THE HISTORICAL SIGNIFICANCE OF MAHMUDKHOJA BEHBUDI IN NEW UZBEKISTAN EDUCATION REFORMS - Mamadiyorov Ulug’bek Dilshodovich (Galaxy International Interdisciplinary Research Journal, 2023)
It is known that, as a solution to the problems of Turkestan from the point of view of science, it is necessary to ensure welfare and stable development by reforming the education system, to form not only religious but also secular sciences and national tolerance in the public mind. Scientific ideas lead to advanced sciences. Today, the importance of Mahmudhoja Behbudi’s ideas of common scientific heritage is being studied as a valuable resource for the development of modern education in Turkestan in the late 19th and early 20th centuries.